Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 7 - 7.1 - Using Fundamental Identities - 7.1 Exercises - Page 513: 36



Work Step by Step

We know that: $sec~x=\frac{1}{cos~x}$ $sin^2x+cos^2x=1$ $sin^2x=1-cos^2x$ So: $cos~x(sec~x-cos~x)=cos~x(\frac{1}{cos~x}-cos~x)=1-cos^2x=sin^2x$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.